Pengaruh Model Pembelajaran Discovery Learning Terhadap Kemampuan Pemahaman Konsep Matematis Siswa Kelas IX SMP Negeri 5 Sumbul - Sihotang, Verawaty (Unika Santo Thomas Medan, 2018)
This study aims to determine the ability to understand the mathematical concepts of students who take part in learning with the discovery learning model higher than the ability to understand the mathematical concepts of students who follow conventional learning and student responses to the discovery learning model. This research was conducted at 5 Sumbul Junior High School inÂ 2017/2018 Academic Year. The sample in this study was class IX-1 as an experimental class as many as 35 people and class IX-2 as a control class of 35 people. The research method used was the quasi-experimental method with the design of pretest-posttest control in group design. Hypothesis test results show at the significance level = 0.05 the value of t count = 4.964> t table = 1.667. So that H0 is rejected and Ha is accepted, which means that the ability to understand the mathematical concepts of students who take part in learning with the discovery learning model is higher than the comprehension abilities of students who take conventional learning. The results of the questionnaire analysis of student responses to the discovery learning model were obtained: (1) 98.57% of students were interested; (2) 96.67% of students stated that there were benefits obtained; (3) 75% of students stated that there were no obstacles experienced during the learning process; and (4) 84.76% of students hope that the discovery learning model is used in the learning process. This shows that the positive student response to the discovery learning model.